KERAGAMAN RAYAP RHINOTERMITIDAE (ISOPTERA, INSEKTA) DI HUTAN PENDIDIKAN UNIVERSITAS HASANUDDIN: Diversity of Rhinotermitidae (Isoptera, Insecta) on Education Forest of Hasanuddin University - Astuti Arif; Giselawati Putri; Pertiwi Indah Lestari; Widawati Widawati; Maftukha Nurqalbi; Adam Saira (PERENNIAL, 2020)
Rhinotermitidae is a family with many species which are pests to plants and buildings. This study aims to identify the species belonging to the Rhinotermitidae. The morphological characteristics of specimens collected by using the transect sampling protocol of forest types (natural forest, pine plantation, and mahogany plantation) in the Educational Forest were observed. The results showed that the number of termite specimens differed from each forest type, namely 36.4% obtained in natural forests, 38.4% in mahogany plantations, and 25.2% in pine plantations. The total of collected termites was 258 specimens, mostly members of Termitidae (67.4%) and others including members of Rhinotermitidae (32.6%). Based on morphological characteristics of the soldier of Rhinotermitidae, only two species were identified, namely Coptotermes curvignathus (Coptotermitinae) and Schedorhinotermes sp. (Rhinotermitinae) with a predominance of 88.5%.